An Observational Study on the Functional Outcomes of Intramedullary Nailing Versus Dynamic Compression Plating for Humeral Shaft Fractures - Usman Zafar Dar, Mohammad Nauman Shahid, Ali Muqaddas, Sameer Ahmed, Muhammad Ahmed, Naeem Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The purpose of this research is to evaluate and contrast the functional results of Dynamic Compression Plating and Interlock Nailing for Humeral Shaft Fractures. Material and Methods: The design of this study was a prospective observational study. This study was conducted in DHQ Teaching Hospital Gujranwala and the duration of this study was from October 2020 to December 2022. We evaluated a total of 60 cases after receiving ethics committee permission from our institute. In DHQ Teaching Hospital Gujranwala, a study on instances of humeral shaft fractures needing surgical intervention was conducted. Results: In the plating group, 76.7% of the cases had outstanding results, compared to 56.7% in the nailing group. Moreover, the nailing group had a worse overall result (13.4% vs. 10%). Conclusion: Locking plating and intramedullary nailing had statistically similar results for individuals undergoing surgical intervention for humeral shaft fractures. In terms of union and function, both provide excellent and favourable results, but the dynamic compression plating group had a higher percentage of positive results and a propensity for union. Keywords: Humeral Shaft Fracture, Intramedullary Nailing, Dynamic Compression Plating